On coc-r-compact spaces - Aziz Hussain Al-Abdulla, Raad; Attala Shneef, Fadhel (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this.work, We will study a.new class of popularizer open.sets called.coc-r-open sets and we will study its properties too, also we will study coc-r-compact, I-Compact space and the relationship between them, finally we have to get some results that show the relationship between these spaces through some of the theorems obtained by using coc-r-open sets.